COMPENSATORY COMPETENCE IN FOREIGN LANGUAGE LEARNING: A STRATEGIC ADVANTAGE - Ishonkulov Sherzod Usmonovich (Western European Studies, 2024)
This paper explores the concept of compensatory competence in the field of foreign languages. It defines compensatory competence as the ability to leverage strengths in one language skill to overcome weaknesses in another. The paper discusses the various forms this competence can take, its benefits for language learners, and strategies for developing it. Additionally, the paper examines the role of compensatory competence in achieving fluency and proficiency in a foreign language.
Keywords: Compensatory competence; foreign language learning; language skills